Detection of new regulatory SNPs associated with colorectal cancer predisposition - E. Yu. Leberfarb; L. O. Bryzgalov; I. I. Brusentsov; T. I. Merkulova (Вавиловский журнал генетики и селекции)
A new approach to the search for regulatory SNPs (rSNPs) based on the use of ENCODE project data on ChIP-seq and RNA-seq experiments was developed. The approach was successfully used for the detection of rSNPs associated with colorectal cancer susceptibility. To start out with, we used raw sequence data of 15 independent ChIP-seq experiments run on colorectal cancer cell line HCT-116, which allowed us to generate the initial pool of 7985 SNPs located in regulatory regions. For further selection of functional SNPs, we used the ChIP-seq binding bias analysis and revealed 775 SNPs that are more likely to influence transcription regulation in HCT-116 cells. Then the RNA-seq bias analysis in HCT-116 cells was performed. As a result, we confirmed the functionality of 231 SNPs, which were classified as rSNPs. In order to select rSNPs potentially associated with colorectal cancer we chose those in strong linkage disequilibrium with SNPs asso-ciated with this pathology according to GWAS and ClinVar data. Functional annotation analysis of genes containing the rSNPs selected confirmed the involvement of BAIAP2L1 and BUB3 genes in colorectal cancer predisposition. We also found two genes (RRAGD and FZD6) playing a role in the RAS/MAРK and WNT signaling pathways. Although the involvement of the RAS/MAРK and WNT pathways in colon cancer is a well-known fact, these two genes are still unknown candidates. Moreover, we found 14 new candidate genes with promise for further study of colorectal cancer predisposition.